Cognitive-behavioral and electrophysiological evidence of the affective consequences of ignoring stimulus representations in working memory - De Vito, D; Ferrey, A; Fenske, M; Al-Aidroos, N (Springer US, 2018)
Ignoring visual stimuli in the external environment leads to decreased liking of those items, a phenomenon attributed to the affective consequences of attentional inhibition. Here we investigated the generality of this “distractor devaluation” phenomenon by asking whether ignoring stimuli represented internally within visual working memory has the same affective consequences. In two experiments we presented participants with two or three visual stimuli and then, after the stimuli were no longer visible, provided an attentional cue indicating which item in memory was the target they would have to later recall, and which were task-irrelevant distractors. Participants subsequently judged how much they liked these stimuli. Previously-ignored distractors were consistently rated less favorably than targets, replicating prior findings of distractor devaluation. To gain converging evidence, in Experiment 2, we also examined the electrophysiological processes associated with devaluation by measuring individual differences in attention (N2pc) and working memory (CDA) event-related potentials following the attention cue. Larger amplitude of an N2pc-like component was associated with greater devaluation, suggesting that individuals displaying more effective selection of memory targets—an act aided by distractor inhibition—displayed greater levels of distractor devaluation. Individuals showing a larger post-cue CDA amplitude (but not pre-cue CDA amplitude) also showed greater distractor devaluation, supporting prior evidence that visual working-memory resources have a functional role in effecting devaluation. Together, these findings demonstrate that ignoring working-memory representations has affective consequences, and adds to the growing evidence that the contribution of selective-attention mechanisms to a wide range of human thoughts and behaviors leads to devaluation.